Evaluation of Grain Quality and Cooking Property of Selected Local Rice Cultivars in Bangladesh (Journal of Environmental Science and Natural Resources, 2025)
To assess the grain qualities of local rice cultivars, an experiment was carried out on seven varieties i.e., Pajam, Kataribhog, Rata boro, Ganjia, Binnaful, Nizersail, and Jirasail. Several physicochemical traits (length, breadth, moisture content and chalkiness), milling quality (head rice yield and milling outturn), nutritional aspect (protein content) and cooking properties (amylose content, cooking time, grain elongation, water uptake ratio, gel consistency, and gelatinization temperature) were measured. The moisture content (11.10% to 12.17%), protein (6.23% to 10.17%), and amylose content (24.65% to 28.11%) were within the expected ranges in all genotypes. Based on grain milling outturn (%) and head rice yield (%), Pajam and Kataribhog were of premium quality. The appearance quality of Ganjia, Binnafu and Nizersail was better due to having negligible chalkiness. Kaaribhog and Binnaful had shorter cooking times (14±1 min). Rata boro, Ganjia and Nizersail had soft (>61 mm gel), whereas Kataribhog and Jirasail showed medium gel consistency (41- 60 mm gel). Most of the varieties had a low gelatinization temperature (GT) except Jirasail (high GT) and Pajam (intermediate GT). Jirasail significantly outperforms all other genotypes in physicochemical, nutritional, and cooking traits and could be a suitable choice for consumers.Environ. Sci. & Natural Resources, 14(1&2): 1-9, 2025